The Authorization of Cross-Agreement Retaliation for Ecuador in the Banana Dispute - I Gede Ketut Catur Bimantara Suberata (Journal of World Trade Studies, 2013)
The formation of the World Trade Organization (WTO) in 1995 was a step forward to a more organized and rule-binding universal trade regime. The WTO is acknowledged as a rule-oriented institution as it implements a detailed and binding dispute settlement mechanism, for which most developing countries are appreciative. Nevertheless, this mechanism does not overcome the age-old question of how developing countries should go about ensuing developed nations comply with the WTO's rulings. The notion of cross-agreement retaliation is discussed in the article as a possible solution to the aforementioned problem. Cross-agreement retaliation, also commonly known as cross retaliation, enables developing countries to suspend concessions in different agreements, especially in relation to the agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS), which provides crucial concessions for developed countries. Using the most well-known WTO dispute, the Banana War, this article examines the crucial role of cross retaliation. In that case, Ecuador, one of the plaintiffs, was granted the right to cross-retaliate under the TRIPS agreement, yet despite the authorization, it did not enforce its right and subsequently the case dragged on for years. This begs the question of why Ecuador refrained from implementing its right. The instrument of cross retaliation may be used as a precedent for future disputes involving developing countries in the WTO. This article analyzes the reason for Ecuador's decision by examining the complexity of cross-retaliation implementation, the true nature of cross-retaliation, and other significant contributing factors to the dispute.